The State Participatory Budgeting in Rio Grande do Sul. Some Evidences from Pampas - Carbonai, Davide; Gugliano, Alfredo Alejandro; Camiz, Sergio (PARTECIPAZIONE E CONFLITTO, 2017)
The article presents the main results of a survey on voting behavior at the State Participatory Budgeting of Rio Grande do Sul (also known as Consulta popular). The research is based on a sample of 389 respondents, all residents in San Borja, city in the western border of Rio Grande do Sul (Brazil). The article aims to address participation and vote in Consulta popular, considered its role of social inclusion and promotion of political participation. After a brief descriptive analysis, in order to get a better synthetic overview of the data, we submitted the considered characters to two different multidimensional analyses, in search of possible relations among them. The analyses performed were an exploratory one (a Multiple Correspondence Analysis, MCA) and a Generalized Linear Model by hypothesizing a Binomial distribution for the nominal data.